Structural Sensitivity of Tarpon Monopods in Intermediate Water Depths for Marginal Field Development - Eik, Lee Hsiu; Liew, Mohd Shahir (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
The Tarpon Monopod is a minimal platform cable guyed caisson used to develop marginal fields. An in depth structural sensitivity study is performed on the Tarpon platform in 76 m water depth situated in Malaysian waters. An operating Tarpon platform offshore Peninsular Malaysia is modelled in the finite element structural analysis software, SACS v5.3 to reflect the as built condition and simulated to a combination of four different storm design criterion with two dominant approach directions to capture the monsoon seasons in the region. The guying system will be varied by simulating trivial loss of wire ropes from being intact, fully guyed to its damaged, freestanding mode. The results suggest that the Tarpon Monopod has relatively low structural redundancy and its integrity highly depends on its guying system condition. Structural weaknesses are identified alongside proposed key best practices and potential improvements to the platform.